Adsorption Isotherms for Phenol Onto Activated Carbon - Hawaiah Imam Maarof; Bassim H. Hameed; Abdul Latif Ahmad (ASEAN Journal of Chemical Engineering, 2004)
This laboratory study investigated the effectiveness of two types of activated carbons (ACs), NORIT Granular Activated Carbon (NAC 1240) and NORIT Granular Activated Carbon 010 (NAC 010), for the removal of phenol from aqueous solutions. The study was carried out under batch mode at different initial concentrations (10-60 mg/I) and at temperature of 30°C. The adsorption isotherm parameters for the Langmuir and Freundlich models were determined using the adsorption data. It was found that both the Langmuir and the Freundlich isotherms described well the adsorption behavior of phenol on NAC 010, while the Freundlich isotherm described very well the adsorption of phenol on NAC 1240.